Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Motivasi Kerja Terhadap Disiplin Kerja Pegawai Di Laboratorium KESMAVET PUSYANKESWANNAK Bambu Apus - Tussa’diyah, Nurhalimah; Siswani, Sri (JURNAL ADMINISTRASI & MANAJEMEN, 2024)
The problem in this research is the low work discipline of employees at the Pusyankeswannak Bambu Apus Veterinary Public Health Laboratory, which can be seen from the employees often arriving late. This research aims to examine the influence of Leadership Style, Work Environment, and Work Motivation on Employee Work Discipline at the Pusyankeswannak Bambu Apus Veterinary Public Health Laboratory. This research uses a quantitative approach with the research location at the Pusyankeswannak Bambu Apus Veterinary Public Health Laboratory. Data was collected through a Likert scale questionnaire which was distributed to 35 employees in the laboratory. Respondents were selected using saturated sampling techniques. Data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method using the SmartPLS 4 program. Hypothesis test results show that leadership style has a positive and significant effect on work discipline, the work environment has a negative and significant effect on work discipline, and work motivation has a positive and significant effect on work discipline. Keywords: leadership style, work environment, work motivation and work disciplin